Agglomeration Externalities in the Productivity of Indonesian Furniture Companies: Survey of Medium-Large Manufacturing Companies in 2010-2015 - Jamhari, Muhammad; Santosa, Purbayu Budi; SBM, Nugroho (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at measuring the externalities of agglomeration on productivity of furniture companies in Indonesia. The data used is a pannel data obtained from the survey of medium-large manufacturing companies during 2010 to 2015. The company’s productivity is measured through Wooldridge One-Stage Production Function Estimation Method (2009). Productivity calculated based on the results of the estimated production function is used as the dependent variable to see the impact of agglomeration. The size of the agglomeration used in this study is the number of similar companies, the number of related weighted companies, the average output of similar companies, and the average output of related weighted companies in one Regency/ area. The results of this study indicate that the agglomeration size of the number of related companies, the average output of similar companies, and the average output of related weighted companies had positive externalities on the productivity of furniture companies, while the number of similar companies showed negative externalities.